ASSA13-14-22 The Changes of Large-Conductance Ca2+-Activated Potassium Channels to AngiotensinII in Human Mesenteric Artery Smooth Muscle Cells During Hypertension. (29th April 2013) - Jing, Wen; Xiaorong, Zeng; Pengyun, Li; Jun, Cheng; Yan, Yang
Abstract : Objective: Angiotensin II (Ang II) is the most important bioactive peptide of renin angiotensin system, combining with its specific receptor, has significant effect on structure and function of the heart and blood vessels. The continuous increasing tension of resistance vessel is the fundamental pathological features of hypertension (HT), and the ion channels on vascular smooth muscle cells (VSMCs) are involved in the regulation of vascular tension. Activation of large conductance calcium-activated potassium channels (BKCa ) is one of the important mechanisms involved in vascular smooth muscle relaxation. AngII relaxes mesenteric artery via stimulation of the angiotensinII type 2 receptor (AT2 R) with subsequent opening of BKCa . It is necessary to investigate the change of AT2 R under the hypertension condition and BKCa change response to AngII. It will expand our understanding of the pathogenesis and development of hypertension. Methods: Using amphotericin-perforated whole-cell recording technique and Western blot analysis, we will know the relationships among AngII, AT2 R and hypertension. Results: (1) In the amphotericin-perforated whole-cell patch-clamp configuration, after pretreatment with Valsartan (a specific inhibitor of angiotensinII type 1 receptor, 10 μmol/L), ➀ In the normotension (NT) group, 100 nmol/L AngII can augment BKCa whole-cell currents in human mesenteric artery VSMCs, the current density of BKCa at the voltage of −60 ∼ +20 mV had no significant change before and after adding 100 nmol/L AngII, but the current density of BKCa at the voltage of +30 mV, +40 mV, +50 mV and +60 mV increased significantly after adding 100 nmol/L AngII, from (5.84 ± 1.25) pA/pF, (9.19 ± 1.54) pA/pF, (13.32 ± 1.83) pA/pF and (18.06 ± 2.13) pA/pF to (8.68 ± 1.70) pA/pF, (13.24 ± 2.00) pA/pF, (19.44 ± 2.14) pA/pF and (28.09 ± 2.62) pA/pF (n = 10, P < 0.05). ➁ In the HT group, AngII had no significant effect on BKCa . (2) The protein amount of the AT2 R in mesenteric artery among the NT group and the HT group was 1.2046 ± 0.0564 (n = 13), 0.9893 ± 0.0543 (n = 6), the expression level of AT2 R protein of the NT group was greater than the HT group ( P < 0.05). Conclusions: AT2 R is downregulated in hypertension, we speculate that the different protein of AT2 R results in the response difference of BKCa channel which mediated by AT2 R.